Effect of harvesting training practices toward harvesting productivity / Mohammad Asyraf Sharin - Sharin, Mohammad Asyraf (Faculty of Plantation and Agrotechnology, 2018)
Training is a necessity in the workplace, without it, employments do not have a firm grasp on their responsibilities or duties. Employment training refers to programs that provide workers with information, new skill or professional development opportunities. In these studies, it focused on relationship between harvesting practices with harvesting productivity and dominant harvesting training factors that influence harvesting productivity. The study was conducted at Mersing and data were taken from the questionnaire based on an analysis of training requirement to improve the productivity of harvesting activities. For bunches identification, practices and harvesting procedure is factor to influence and harvesting productivity to be influenced. Data gathered were analyzed using SPSS and construct for correlation and regression. From the result, bunches identification the way of work and highest factor have given an impact on the harvesting productivity. In conclusion, the most dominant factors toward harvesting production was bunches identification and practices and harvesting procedure. For recommendation, the management estate needs to provide training to employees to improve the harvesting productivity.